Synergistic antitumor immune response mediated by paclitaxel-conjugated nanohybrid oncolytic adenovirus with dendritic cell therapy - Kim, In-Wook; Yoon, A-Rum; Hong, JinWoo; Kasala, Dayananda; Yun, Chae-Ok (Frontiers in Immunology, 2024)
Dendritic cell (DC)-based vaccines have emerged as a promising strategy in cancer immunotherapy due to low toxicity. However, the therapeutic efficacy of DC as a monotherapy is insufficient due to highly immunosuppressive tumor environment. To address these limitations of DC as immunotherapeutic agent, we have developed a polymeric nanocomplex incorporating (1) oncolytic adenovirus (oAd) co-expressing interleukin (IL)-12 and granulocyte-macrophage colony-stimulating factor (GM-CSF) and ( 2) arginine-grafted bioreducible polymer with PEGylated paclitaxel (APP) to restore antitumor immune surveillance function in tumor milieu and potentiate immunostimulatory attributes of DC vaccine. Nanohybrid complex (oAd/APP) in combination with DC (oAd/APP+DC) induced superior expression level of antitumor cytokines (IL-12, GM-CSF, and interferon gamma) than either oAd/APP or DC monotherapy in tumor tissues, thus resulting in superior intratumoral infiltration of both endogenous and exogenous DCs. Furthermore, oAd/APP+DC treatment led superior migration of DC to secondary lymphoid organs, such as draining lymph nodes and spleen, in comparison with either monotherapy. Superior migration profile of DCs in oAd/APP+DC treatment group resulted in more prolific activation of tumor-specific T cells in these lymphoid organs and greater intratumoral infiltration of T cells. Additionally, oAd/APP+DC treatment led to lower subset of tumor infiltrating lymphocytes and splenocytes being immunosuppressive